“Estimulación Temprana en el Desarrollo de la Inteligencia Kinestésica de los niños de tres a cuatro años de la Escuela Particular Nuestro Mundo “Ecorio” de la Ciudad de Riobamba, provincia de Chimborazo, año lectivo 2015-2016” - Catagña Quishpi, Magaly Rocío (2017)
Early stimulation as a strategy for integral development emerges as a group of techniques for the development of the capacities and abilities of children in early childhood, before this background was raised as a general objective, to determine how early stimulation influences the development of Kinesthetic intelligence in children and specifically techniques to observe the level of development acquired by children, the theoretical framework was investigated on the two dependent and independent variables; The methodology used for the realization of the present work was design of non-experimental research which was done without deliberately manipulating the variables, types of research, descriptive and explanatory the same that was used to describe fundamental aspects, correlational in the execution of the variables , level; Descriptive: he referred to social phenomena in a given temporal and geographical circumstance. The study population was the 70 children aged 3 to 4 years, from Initial 2 where the observation technique was applied through the instrument that was the observation sheet, base on which it was possible to conclude that significant childhood helps in the Development of Kinesthetic Intelligence leaving open the possibility of opening the wide range of stimulation for the subsequent application of innovative techniques that contribute to strengthen initial training processes